Estimation of Curve Number and runoff of a microwatershed using Soil Conservation Service Curve Number method - CHANU, SANJARAMBAM NIRUPAMA; THOMAS, ALEX; KUMAR, PRAVENDRA (Journal of Soil and Water Conservation, 2021)
Since most of the Indian watersheds are ungauged, estimation of runoff depth is one of the key parameter not only for designing engineering structures in watershed but also for prioritization of sub watersheds within the watershed. Present study was undertaken to determine the runoff depth using the USDA Soil Conservation Service curve number (SCS-CN) method in Dadri Mafi micro-watershed, located between 25° 4´ 32.47´´ to 25° 6´ 27.47´´ N Latitude and 80° 28.11´´ to 80° 55´ 41.59´´ E Longitude which is situated at Manikpur block of Chitrakoot district, Uttar Pradesh. A total of 30 single storm events were selected between the years 2004 and 2012 for present study. Antecedent moisture condition (AMC) was calculated by taking preceding five days rainfall which gave three conditions AMC I, AMC II and AMC III. Weighted Curve Number for the entire selected micro-watershed was calculated based on site information of the watershed and found to be 82.40 for AMC II. The CN values corresponding to AMC I and AMC III were 66.28 and 91.50 respectively. The runoff for each storm events was estimated using Curve Number method and it was found that among the selected storm events maximum rainfall of 184 mm occurred on July 7, 2012 giving runoff value of 158.44 mm and minimum rainfall of 35 mm occurred on July 13, 2009 with runoff value of 0.61 mm. Runoff volume of the micro-watershed for each storm events were also calculated and maximum runoff was found be 918499.37 m³. Strong correlation has been observed between rainfall and estimated runoff as well as observed and estimated runoff which indicate applicability of SCS-CN method in predicting runoff for the study area.